2022
DOI: 10.1111/jfs.12983
|View full text |Cite
|
Sign up to set email alerts
|

Use of ComBase data to develop an artificial neural network model for nonthermal inactivation of Campylobacter jejuni in milk and beef and evaluation of model performance and data completeness using the acceptable prediction zones method

Abstract: ComBase is a widely used microbial modeling database. ComBase data can be used to develop and validate models and to test novel modeling methods like artificial neural networks (ANN) and acceptable prediction zones (APZ), which have been shown to outperform traditional methods. Here, ComBase data were used to evaluate the ANN and APZ methods for modeling nonthermal inactivation of Campylobacter jejuni in milk and beef as a function of time, temperature (À20, 1, 10, 20, 30, and 40 C), and strain (18177, ATCC 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The minimum temperature was used for the analysis since the teat swab samples were taken early in the morning. Previous in vitro studies demonstrated a slower inactivation of C. jejuni by oxygen at cooler temperatures [ 37 , 38 , 39 ]. This was not observed in our study, as all classes of results occurred in the same temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum temperature was used for the analysis since the teat swab samples were taken early in the morning. Previous in vitro studies demonstrated a slower inactivation of C. jejuni by oxygen at cooler temperatures [ 37 , 38 , 39 ]. This was not observed in our study, as all classes of results occurred in the same temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…C. jejuni only grows under special conditions, that is, at high temperatures and low oxygen levels, and in general, its non‐thermal inactivation by oxygen is slower at cold temperatures (Boleratz & Oscar, 2022; Olofsson et al, 2015; Yoon et al, 2004). Additionally, Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies investigated the survival of different strains of Campylobacter spp. in raw, skimmed or unpasteurized milk at distinct temperatures (Boleratz & Oscar, 2022; Christopher et al, 1982; Doyle & Roman, 1982; Jaakkonen et al, 2020; Wulsten et al, 2020), and only one investigated the possibility of survival of Campylobacter spp. in VBNC state in raw milk (Wulsten et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Logistic Regression (Cox 1958 [ 2 ]) and Random Forest (Ho 1995 [ 3 ], Breiman 2001 [ 4 ]) are widely used for modeling and drawing useful inferences about zoonotic diseases and their transmission (Ntampaka et al, 2021 [ 5 ], Kiambi et al, 2020 [ 6 ], Acharya et al, 2019 [ 7 ]). More recently, the effectiveness of artificial neural networks in modeling zoonotic diseases and their causes have also been demonstrated in a number of studies (Boleratz and Oscar 2022 [ 8 ], ZareBidaki et al, 2022 [ 9 ], Denholm et al, 2020 [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%